Proses Manufaktur Piston Displacer untuk Mesin Stirling Tipe Gamma Skala Kecil - Aldi Kurniawan; Jufrizal Jufrizal; Nurdiana Nurdiana (CV. IRA PUBLISHING, 2025)
This study aims to design and manufacture a displacer piston for a Gamma-type Stirling engine using steam pipe material due to its heat-resistant properties. The manufacturing process involved cutting, turning with a conventional lathe, and TIG welding. The final product dimensions were 65.75 mm in diameter, 60.20 mm in height, and 321.20 mm. Measurement results showed that the dimensional tolerances were within the design limits, and no leakage was found in the joints after visual inspection and basic functional testing. The study demonstrates that a simple process can produce a piston suitable for laboratory-scale applications.